Evropsko potrdilo o dedovanju - Rijavec, Vesna (Podjetje in delo, 2016)
The contribution discusses problems of European Certificate of Succession (ESC) in Succession Regulation (EU) 650/2012 to study its characteristics from the point of view of national law, which applies when the Regulation doesn't determine otherwise. For the understanding of the scope and meaning of the new instrument, the examples followed by the European legislator are of great importance. The author comments the procedural rules, international jurisdiction, competence of the issuing authority, issue of ESC, scope and nature of ESC, effects and legal remedies. ESC can only be issued when the estate of a deceased is situated in at least two different member states, its use is not mandatory and it does not replace the national title, its scope is limited to certify the status of heirs, legatees having direct rights in the succession and executors of wills or administrators. The effect of ESC doesn't extend over preliminary questions for the succession right. The author discusses the problems of multiple procedures on the same succession.
Keywords: dedno pravo; dedovanje; Evropa; Evropska unija